2021
DOI: 10.1186/s12964-021-00779-y
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-mediated activation of CREB pathway in proliferation of pulmonary artery smooth muscle cells in pulmonary hypertension

Abstract: Background Transcription factor CREB is involved in the development of pulmonary hypertension (PH). However, little is known about the role and regulatory signaling of CREB in PH. Methods A series of techniques, including bioinformatics methods, western blot, cell proliferation and luciferase reporter assay were used to perform a comprehensive analysis of the role and regulation of CREB in proliferation of pulmonary artery smooth muscle cells (PASM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Moreover, it has recently been shown that ZIP12 plays an important role in the hypoxia-induced phenotypic transition of PASMCs [ 32 ]. In our recently published work, we demonstrated that elevated intracellular labile zinc possibly from ZIP12 was associated with increased CREB-mediated transcriptional activity and PASMCs proliferation [ 16 ]. However, functional characterization is further required for ZIP12 via the transgenic approaches including the gene overexpression and silencing analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has recently been shown that ZIP12 plays an important role in the hypoxia-induced phenotypic transition of PASMCs [ 32 ]. In our recently published work, we demonstrated that elevated intracellular labile zinc possibly from ZIP12 was associated with increased CREB-mediated transcriptional activity and PASMCs proliferation [ 16 ]. However, functional characterization is further required for ZIP12 via the transgenic approaches including the gene overexpression and silencing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…ZIP12 knockdown was shown to inhibit hypoxia-induced influx of zinc ions and subsequent proliferation of the cells, ameliorate pulmonary arterial remodeling, and suppress elevated pulmonary arterial pressure [ 15 ]. Our previous study [ 16 ] and another recent study [ 17 ] have demonstrated that ZIP12 expression is upregulated in MCT-induced PAH. However, the role of ZIP12 in mechanisms of MCT-induced PAH rats have not been described previously.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that altered zinc and zinc transporter protein levels are associated with the occurrence and progression of PH [ 34 , 35 , 36 , 37 ]. A previous study by Zhao et al identified that plasmalemma zinc transporter ZIP12, encoded by the gene Slc39a12, plays a critical role in hypoxia-induced pulmonary vascular remodeling [ 34 ].…”
Section: The Role Of Zinc Dyshomeostasis In Lung Diseasementioning
confidence: 99%
“…While the results of these studies point to ZIP12 having a fundamental role in regulating pulmonary vascular homeostasis and remodeling under hypoxic conditions, the underlying mechanisms of how ZIP12 affects hypoxic responses remain unclear. Another study by Xiao et al demonstrated that increased intracellular labile zinc, possibly from ZIP12, was linked with reduced phosphatases, increased transcription factor CREB-mediated activity, and PASMC proliferation [ 35 ]. Zhu et al showed that ZIP12 contributed to phenotypic switching in hypoxia-induced PASMCs and promoted PH.…”
Section: The Role Of Zinc Dyshomeostasis In Lung Diseasementioning
confidence: 99%
“…CREB gene knockout mice had embryonal neuronal deficits and a reduced lifespan [ 2 , 3 ]. The dysregulation of the CREB gene results in aberrant signal transduction affecting apoptosis, proliferation and differentiation, immune surveillance, and metabolism [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%